Effect of post weld heat treatment on mechanical properties of inconel 718 alloy - Toe, Thu Yein (2017)
In this study, only two mechanical properties, hardness and fatigue, were considered. Most of the aerospace components requirement high impact toughness, high corrosion resistance and good fracture toughness. Considering other important mechanical properties to determine an optimum PHWT temperature will make the analysis more realistic.